Research in Creative Arts Therapies: When Counselling and the Arts Meet - Newcomb, M. Melody; Centeno, Isabel M. (Canadian Journal of Counselling and Psychotherapy, 2020)
The focus of this special issue of Canadian Journal of Counselling and Psychotherapy is on the use of arts in counselling. Considerations are given to creative arts therapists and to professional counsellors who use creative arts interventions in their practice. Issues regarding research involving arts practice are raised, and the ethics of practitioners and the ways in which art is part of research are discussed. Studies are presented involving a variety of populations covering the lifespan of children, young adults, and older adults and including Indigenous residential school survivors. Various art practices are also used, including art therapy, music therapy, sand tray therapy, play therapy, theatre creation, writing, and creative practices embedded in Indigenous cultures. The arts are integral to life, and their application in counselling, treatment, and research needs to be done thoughtfully and responsibly. Collaboration among creative arts therapists, artists, counsellors, and researchers can only benefit those we serve. We conclude the introduction with an overview of the 11 articles that make up this special issue.